Mutual Stabilization of Rhythmic Vocalization and Whole-Body Movement - Miyata, Kohei; Kudo, Kazutoshi (PLOS ONE, 2014)
The current study investigated the rhythmic coordination between vocalization and whole-body movement. Previous studies have reported that spatiotemporal stability in rhythmic movement increases when coordinated with a rhythmic auditory stimulus or other effector in a stable coordination pattern. Therefore, the present study conducted two experiments to investigate (1) whether there is a stable coordination pattern between vocalization and whole-body movement and (2) whether a stable coordination pattern reduces variability in whole-body movement and vocalization. In Experiment 1, two coordination patterns between vocalizations and whole-body movement (hip, knee, and ankle joint flexion-on-the-voice vs. joint extension-on-the-voice) in a standing posture were explored at movement frequencies of 80, 130, and 180 beats per minute. At higher movement frequencies, the phase angle in the extension-on-the-voice condition deviated from the intended phase angle. However, the angle of the flexion-on-the-voice was maintained even when movement frequency increased. These results suggest that there was a stable coordination pattern in the flexion-on-the-voice condition. In Experiment 2, variability in whole-body movement and voice-onset intervals was compared between two conditions: one related to tasks performed in the flexion-on-the-voice coordination (coordination condition) that was a stable coordination pattern, and the other related to tasks performed independently (control condition). The results showed that variability in whole-body movement and voice-onset intervals was smaller in the coordination condition than in the control condition. Overall, the present study revealed mutual stabilization between rhythmic vocalization and whole-body movement via coordination within a stable pattern, suggesting that coupled action systems can act as a single functional unit or coordinative structure.